Beiträge zur Insektenfauna der DDR: Lepidoptera - Alucitidae. - Sutter, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1990)
Four species of Alucitidae have been established for the territory of the GDR. Finds of Alucita desmodactyla Zeller were not a available.